PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS POWTOON TEKS LAPORAN HASIL OBSERVASI KELAS X SMA - Rischa Dewi; Mulyanto Widodo; Rian Andri Prasetya (FKIP Universitas Lampung, 2020)
The problem in this research is how the development of learning media based powtoon in text report observasions for tenth grade high school students and how the feasibility of media based powtoon in text report observasions for tenth grade high school students. The purpose of this study is to describe the development of learning media based powtoon in text report observasions for tenth grade high school students and to describe the feasibility of media based powtoon in text report observasions for tenth grade high school students. This research uses research and development (rd) method. The result of this study is the creations of learning media based powtoon in text report observations for tenth grade high school students has been validated. Validation is conducted by expert lecturers to test the feasibility of product. The result of the validation is from material expert obtained an average percentage 82% and the the media expert obtained an average percentage 81.25%. Masalah dalam penelitian ini adalah bagaimana pengembanganmedia pembelajaran berbasis powtoon teks laporan hasil observasi kelas X SMAdan bagaimana kelayakan media pembelajaran berbasis powtoon teks laporan hasil observasi kels X SMA. Tujuan penelitian ini untuk mendeskripsikan pengembanganmedia pembelajaran berbasis powtoon teks laporan hasil observasi kelas X SMAdan mendeskripsikan kelayakan media pembelajaran berbasis powtoon teks laporan hasil observasi kelas X SMA. Penelitian ini menggunakan metode research and development (rnd).Hasil penelitian ini ialah terciptanya produk media pembelajaran berbasis powtoon teks laporan hasil observasi kelas X SMA yang sudah divalidasi.Validasi dilakukan oleh dosen ahli untuk menguji kelayakan produk.Hasil validasi dari ahli materi diperoleh rata-rata persentase 82% dan ahli media diperoleh rata-rata persentase 81,25%. Keywords: media development, powtoon, text report observations